Agricultural Trade Balance and Food Self-Sufficiency: Implications for Sustainable Development in Nigeria (2011)
Nigeria used to boast of high surplus in agricultural trade and food self-sufficiency, especially in the 1960s. Today, Nigeria has lost the leading position it once occupied as it is now a major importer of food and agricultural commodities. Nigeria now spends billions of naira on importation of food and agricultural products. This situation is paradoxical as Nigeria is well-endowed with the requisite natural and human resources needed to be food self-sufficient. Besides, most governments are adjudged as successful or failure on the basis of meeting the basic needs of their citizens in terms of food. This study analyzed agricultural trade and food self-sufficiency in the context of policy development scenarios including, the Millennium Development Goals (MDGs) and democratic governance paradigms. Data used for the analyses spanned from 1970 to 2007. Descriptive and trends analyses were employed to analyse agricultural trade variables. Statistical inferences were drawn from the comparative analysis of the policy development scenarios. Agricultural imports for the study period witnessed increasing trend. There was agricultural trade imbalance as Nigeria remained a net importing nation. In all development policy scenarios, there were significant (p<0.01) increases in total imports, total exports and net imports. Overall, national food self-insufficiency averaged 29.35 (± 4.08) percent. Therefore, with 71 percent level of food self-sufficiency and high levels of food and agricultural commodities importation, Nigeria needs effective food and agricultural policy in form of import-substitution and building on comparative and competitive advantages to redirect and reverse the negative agricultural trade balance to favour improved domestic food production, agricultural industrialization and value addition with a view to ensuring sustainable agricultural and economic development in Nigeria.